2021
DOI: 10.4271/2021-01-0536
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Gasoline Direct Injection Engine Emissions for the First 5 Firing Cycles of Cold Start

Abstract: <div class="section abstract"><div class="htmlview paragraph">A series of cold start experiments using a 2.0 liter gasoline turbocharged direct injection (GTDI) engine with custom controls and calibration were carried out using gasoline and iso-pentane fuels, to obtain the cold start emissions profiles for the first 5 firing cycles at an ambient temperature of 22°C. The exhaust gases, both emitted during the cold start firing and emitted during the cranking process right after the firing, were capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…where D is the fractal dimension, which quantitively characterizes the degree of the flame wrinkling; L max is the maximum flame wrinkling scale, which is larger than the integral length scale (L i ), as in equation (3) shown in previous studies, 17,19 or equals the instantaneous flame radius in the early combustion phase when the flame radius is still smaller than L i ; L min is found to be larger than the Kolmogorov length scale (h) in the aforementioned studies, as shown in equation (4).…”
Section: Details Of the Fes Modelmentioning
confidence: 78%
See 1 more Smart Citation
“…where D is the fractal dimension, which quantitively characterizes the degree of the flame wrinkling; L max is the maximum flame wrinkling scale, which is larger than the integral length scale (L i ), as in equation (3) shown in previous studies, 17,19 or equals the instantaneous flame radius in the early combustion phase when the flame radius is still smaller than L i ; L min is found to be larger than the Kolmogorov length scale (h) in the aforementioned studies, as shown in equation (4).…”
Section: Details Of the Fes Modelmentioning
confidence: 78%
“…It has been reported that more than 90% of hydrocarbon (HC) emissions originate from the first 2 min of engine operation when the temperature of the catalysts is low. 2 In the cold start process, the very first firing cycle deserves special attention, as most HCs come out during this cycle, and then gradually decrease during subsequent cycles, as shown by prior cycle-resolved cold start experiments 3,4 by our research team. The fuel rail pressure (FRP) is much lower when the engine is first started during the very first firing cycle, and the cold walls in the engine make the fuel film evaporation very slow, resulting in more fuel injected for compensation and leading to more mixture stratification in the cylinder.…”
Section: Introductionmentioning
confidence: 90%
“…18 Malaguti et al 19 carried out numerical simulation methods to analyze the fuel evaporation and fuel film formation process in the first two firing cycles. Previous research from our research group proposed 12 and validated 20 a novel experimental technique that quantified engine-out emissions for each of the first five firing cycles. In addition, a simulation model that focused on the transient engine speed and fuel rail pressure on in-cylinder injection parameters and combustion was used to gain additional insights, as well.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the catalysts in the after-treatment system cannot be fully operational because the temperature is below the light-off temperature of around 250°C. 2 Different experimental [3][4][5][6] and simulation [7][8][9][10][11] studies have been used to focus on what happens during the cold start process and what may be done to reduce the emissions. Efforts are needed in the experiments to eliminate the wall wetting and maintain a cold wall to mimic a cold-start environment, which introduces extra work and difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the initial combustion was the slowest in cylinder 3, though the later combustion was the strongest, as explained below, compared to the other cylinders.The fuel spatial distribution at the time of ignition is another key parameter for GDI engines, which is indicated by the standard deviation (f STD ) shown as the yellow curve in Figure8. The standard deviation was calculated following equation(3), where f represents the equivalence ratio, m indicates the mass of the mixture, and the subscripts cell, ave, and total mean the cell, average and total value, respectively.…”
mentioning
confidence: 99%